Human Rights of Working Women & Violation with Special References to India: - (Journal of Advances and Scholarly Researches in Allied Education, 2018)
India have been the sufferers from past. In prior circumstances as well as, have women needed to confront separation, bad form and disrespect. The crime done against the women are despite being given rights equivalent to men. These focuses put a concentration that proceeds with violation of human rights of women in India. The Indian women misuse isn't the present marvel.Or maybe she is being abused from the early circumstances. The women in Indian culture never remained for a reasonable status. Keywords- human rights, working women, violation